1984
DOI: 10.1172/jci111620
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin stimulates tissue plasminogen activator release from cultured human endothelial cells.

Abstract: Abstract. The effect of thrombin on the release of tissue plasminogen activator from endothelial cells was studied in primary cultures of human umbilical vein endothelial cells. Tissue plasminogen activator concentration in conditioned medium was measured by a two-site radioimmunometric assay. The addition of increasing concentrations (0.01 to 10 U/ml) of thrombin to confluent cultures produced a saturable, dose-dependent increase in the rate of release of tissue plasminogen activator. A sixfold increase in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
2
7

Year Published

1994
1994
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(145 citation statements)
references
References 27 publications
6
129
2
7
Order By: Relevance
“…We repeat this procedure for tPA generation by endothelial cells, be it constitutive (see control cells in Schrauwen et al (1994a,b), Schrauwen et al (1995), and data for first 6 h in Levin et al (1984)), or (rapid) induced by thrombin (Schrauwen et al, 1995;data in Booyse et al (1986) is the earliest record of this rapid release, but it is qualitative and cannot be reduced to a form that is usable), or induced by fibrin (Kaplan et al, 1989). We neglect the delayed activation of endothelial cells by thrombin which occurs after 6 h (Levin et al, 1984), since we will perform numerical simulations for less than 1 h (see section 'Procedure for Corroboration of Model with Experimental Data').…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…We repeat this procedure for tPA generation by endothelial cells, be it constitutive (see control cells in Schrauwen et al (1994a,b), Schrauwen et al (1995), and data for first 6 h in Levin et al (1984)), or (rapid) induced by thrombin (Schrauwen et al, 1995;data in Booyse et al (1986) is the earliest record of this rapid release, but it is qualitative and cannot be reduced to a form that is usable), or induced by fibrin (Kaplan et al, 1989). We neglect the delayed activation of endothelial cells by thrombin which occurs after 6 h (Levin et al, 1984), since we will perform numerical simulations for less than 1 h (see section 'Procedure for Corroboration of Model with Experimental Data').…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
“…We neglect the delayed activation of endothelial cells by thrombin which occurs after 6 h (Levin et al, 1984), since we will perform numerical simulations for less than 1 h (see section 'Procedure for Corroboration of Model with Experimental Data'). Again,…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, coordinated induction of both tPA and PAI-1 has been reported with thrombin or basic fibroblast growth factor (bFGF), whereas histamine, activated protein C, and phorbol ester induce tPA alone, and lipopolysaccharide (LPS), transforming growth factor-ß, interleukin-1 (IL-1), or tumor necrosis factor-alpha (TNF-alpha) induce PAI-1 alone. [33,56,76,[102][103][104][105] It has been shown that human systemic endothelial cells in vitro secrete more tPA when exposed to an arterial level of shear stress [26] and pulsatile stretch, [63] whereas PAI-1 secretion remains unaffected. It has been also demonstrated that tPA secretion and tPA mRNA are significantly upregulated after serial passages in culture, whereas the urokinase-type plasminogen activator gene that is normally not expressed in primary culture, becomes quite active at higher passage numbers.…”
Section: Fibrinolytic Mechanismsmentioning
confidence: 99%
“…Previous studies have shown that production of plasminogen activators and inhibitors in various cell types is modulated by several compounds; eg, TPA synthesis in ECs is increased by various stimuli, such as thrombin, 4 histamine, 5 butyrate, 6 retinoic acid, 78 and tumor-promoting agents like phorbol 12-myristate 13-acetate. 9 Factors that modulate PAI-1 expression in ECs include lipopolysaccharides, 10 thrombin, 11 interleukin-1, 12 tumor necrosis factor-a, 13 transforming growth factor-/}, basic fibroblast growth factor, 14 and EC growth supplement (ECGS) combined with heparin.…”
Section: ;14:1040-1046)mentioning
confidence: 99%